Are interventions supporting separated parents father inclusive? Insights and challenges from a review of programme implementation and impact. Issue 2 (10th June 2016) - Philip, Georgia; O'Brien, Margaret
Abstract: This paper reviews divorce‐related parenting programmes, assessing the extent to which fathers are included and whether father inclusion influences outcomes. The paper also discusses limitations of the research evidence and implications for future intervention and evaluation design. Thirteen programmes met the criteria in the review period 2005–2012 but only four had been evaluated using randomized control trials or with independent measures from mothers and fathers. Analysis of these four programmes shows modest evidence of reduced couple‐conflict, improved coparenting and some evidence of improved child outcomes. Key issues raised are the need for improving the quantity and quality of demographic data about fathers; the importance of incorporating analysis by gender of parent into evaluation design and the value of developing and routinely using father‐related indicators to measure programme impact on men's parenting, fathering and co‐parental relationships.